2013
DOI: 10.1177/1948550613484179
|View full text |Cite
|
Sign up to set email alerts
|

Humble Self-Enhancement

Abstract: Abstract:Prior research has linked religiosity to certain forms of self-enhancement. We extend this literature by three studies linking religiosity to the well-established better-than-average effect.First, a reanalysis of self-judgments of desirable characteristics in 15 nations showed that the better-than-average effect was stronger in more religious countries, even taking into account GDP, interdependence, and economic inequality. Second, in two online surveys totaling 1000 Americans, the better-than-average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
4
11
0
Order By: Relevance
“…Three key findings were observed. First, consistent with previous research (Eriksson & Funcke, 2014;Rowatt, Ottenbreit, Nesselroade, & Cunningham, 2002;Sedikides & Gebauer, 2010), religious participants showed evidence of self-enhancement. Specifically, when evaluating themselves in terms of warmth and extraversion, they tended to evaluate themselves higher than did non-religious participants, even after controlling for how they generally rate others and how others rate them.…”
Section: Discussionsupporting
confidence: 89%
“…Three key findings were observed. First, consistent with previous research (Eriksson & Funcke, 2014;Rowatt, Ottenbreit, Nesselroade, & Cunningham, 2002;Sedikides & Gebauer, 2010), religious participants showed evidence of self-enhancement. Specifically, when evaluating themselves in terms of warmth and extraversion, they tended to evaluate themselves higher than did non-religious participants, even after controlling for how they generally rate others and how others rate them.…”
Section: Discussionsupporting
confidence: 89%
“…We would, therefore, expect based on social identity theory (Tajfel & Turner, 1986) that the perceived self-other differences is larger when rating the values of a disliked outgroup than when rating the values of one's own country, because seeing oneself as higher on important values might increase the feeling of superiority toward the outgroup. Indeed, it was found that religious people see other religious ingroup members even more positively than themselves (Eriksson & Funcke, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the controls reduced the possible impact of ingroup bias (in this case, overly positive perceptions of an acquaintance who shares one's faith; Eriksson & Funcke, 2014;Johnson, Ro-30-area-level religiosity watt, & LaBouff, 2012). Finally, controlling for informants' selfreports could effectively control for individual differences in in formants' general scale use (e.g., acquiescence tendency, Zuckerman, Knee, Hodgins, & Miyake, 1995;extreme scoring, Hui & Triandis, 1989).…”
Section: Study 2: Cross-sectional Informant Reportmentioning
confidence: 99%